Chemical synthesis of membrane proteins: a model study on the influenza virus B proton channel. Issue 8 (2nd February 2018) - Baumruck, A. C.; Tietze, D.; Steinacker, L. K.; Tietze, A. A.
Abstract : NCL results in the quantitative yield of a membrane protein, where a thioester peptide is formed from an oxo-ester with an in situ cleavable solubilizing tag. Abstract : In the present study we have developed and optimized a robust strategy for the synthesis of highly hydrophobic peptides, especially membrane proteins, exemplarily using the influenza B M2 proton channel (BM2(1–51)). This strategy is based on the native chemical ligation of two fragments, where the thioester fragment is formed from an oxo-ester peptide, which is synthesized using Fmoc-SPPS, and features an in situ cleavable solubilizing tag (ADO, ADO2 or ADO-Lys5 ). The nearly quantitative production of the ligation product was followed by an optimized work up protocol, resulting in almost quantitative desulfurization and Acm-group cleavage. Circular dichroism analysis in a POPC lipid membrane revealed that the synthetic BM2(1–51) construct adopts a helical structure similar to that of the previously characterized BM2(1–33).